Strategies of the russian companies in difficult economic conditions - A. V. Stepanyan (Стратегические решения и риск-менеджмент, 2018)
Studying the performance of industrial companies in difficult economic conditions represents an actual scientific objective given that Russian companies are faced to identify new ways of development in the conditions of sanctions of the Russian economy and instability of economic development. The article includes generalization of the factors and conditions determining "difficult economic conditions"; definition of threats and opportunities of the Russian industrial companies; the description of the strategies already accepted by the companies in difficult economic conditions The article also includes the comparative analysis of substantial aspects of strategy of the Russian industrial companies. It appears that the most widespread strategy applied by the Russian industrial companies in the conditions of recession, especially in short-term perspective is the retrenchment strategy. The imposed sanctions and the state policy of import substitution are regarded as the stimulus for the industrial companies to revise the structure of the asset portfolio, to focus on reduction of operational costs and divestment of non-core assets. At the same time, the reduction of costs and assets reduces further capability of the industrial companies for growth and development when the conditions improve and revert to positive trend. The analysis of the strategies of Russian industrial companies identified four groups of strategies applied in difficult economic conditions: moderate product diversification; group protective diversification; rationalising diversification; conservative rationalization. It should be noted that no clear significant relationships were found between recession strategy types and recovery performance. This highlights the diversity of business responses to recession conditions and the uncertainty of subsequent performance outcomes.